Estudo teórico das espécies heterobimetálicas laGa, ceGa, euGa e ybGa em fase gasosa . - Maicon Pierre Lourenco (2009)
The current dissertation deals with the study of electronic structure elucidation of gas phase neutral heterobimetallic species LnGa(Ln=La, Ce, Eu, Yb) using relativistic effective core potentials. Lanthanides are of a great interest in different areas of chemistry: coordination chemistry, organometallic chemistry and catalysis. An expectation is that Ln-Ga species may find hidrocarbon aplication as C-H bond activation with performance expected better than the individual lanthanide elements. This work was inspired by results from recent synthesis of complexes containing a heterobimetalic center, where one metal is a lanthanide and the other is a transition metal. Initially, calculations were performed at ROHF and MCSCF levels for the ground state and a few excited states. The NEVPT2 correlated methods were performed with the purpose of increasing the amount of correlation included in the system. Potential energy surfaces were obtained as well some spectroscopic and electric molecular properties from the three computational methods. The relativistic effects are important in dealing with heavy elements, aiming at investigating this effects in the heterobimetallic species LnGa, the mass-velocity and Darwin operator were individually calculated at MCSCF method. The potential surfaces and the spectroscopic properties were then obtained and compared with the non-relativistic results.